Pengaruh Influencer, Membership Program, dan Instagram Ads Terhadap Minat Pembelian Ulang Customer Brand Coach. (Studi Kasus Coach, Plaza Senayan ) - Hatta, Holila; Adrenanus, Rangga (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
This study aim to analyze the effect of influencer, price promo in form of membership program, and the using of instagram ads on repurchase intention of Plaza Senayan Coach’s customer. Plaza Senayan Coach’s customers were taken as respondents. Both primary and secondary data were gathered. Secondary data were gathered from various sources such as journals, books, and other related publications. Primary data were collected using questionnaire which were distributed to the target respondents with a total of 74 respondents were gathered. Various statistical tests such as validity, reliability and classical assumptions tests were employed. It is suggested that Plaza Senayan Coach should be able to maintain the quality of its membership program, the using of instagram ads and improve more ontheir influencer to enhance repurchase intentionfrom their customers. Further research on, it can use other variables to analyze customer repurchase intention, and also develop research methods such as increasing the number of respondents, sampling techniques, and data analysis techniques